Analisis Wacana Kritis Kajian Norman Fairclough dalam Wacana “Turbulensi Kurikulum Merdeka” Harian Kompas.com - Teti Sobari; Agus Abdurohim; Raden Ika Mustika; Sabila Idzni Suryana (Ranah: Jurnal Kajian Bahasa, 2025)
The implementation of the independent curriculum at the time was a hot issue in education circles, and many ideas responded to the independent curriculum, both pro and con. This study aims to identify the challenges and obstacles in the implementation of the independent curriculum through a three-dimensional analysis: micro, medo, and macrostructure. This study uses a qualitative-descriptive method. The data collection technique was carried out through documentation of the news text entitled "Turbulence of the Independent Curriculum" published by Kompas.com on January 20, 2023. The analysis technique refers to the dialectical-relational approach developed by Fairclough covering three dimensions of analysis, namely microstructure (text analysis), mesostructure (discourse practice), and macrostructure (social practice. The results of the study in the discourse "Turbulence of the Independent Curriculum" from the linguistic aspect found terms that can strengthen the understanding of the independent curriculum, from the aspect of discourse practice the use of language style can provide readers with an understanding of the dynamics of the independent curriculum, then from the aspect of social practice in the discourse there is a relationship between roles in the world of education to synergize in facing and implementing the independent curriculum. Abstrak Implementasi kurikulum merdeka pada saat sedang menjadi isu hangat dikalangan Pendidikan, banyak sekali gagasan yang menanggapi terhadap kurikulum merdeka baik itu yang pro atau kontra. Penelitian ini bertujuan mengindentifikasi tantangan dan hambatan dalam implementasi kurikulum merdeka melalui analisis tiga dimensi: mikrostuktur, mesostuktur, dan makrostuktur. Penelitian ini menggunakan metode kualitatif-deskriptif. Teknik pengumpulan data dilakukan melalui dokumentasi terhadap teks berita berjudul “Turbulensi Kurikulum Merdeka” yang diterbitkan oleh Kompas.com pada 20 Januari 2023. Teknik analisis mengacu pada pendekatan dialectical-relational yang dikembangkan oleh Fairclough mencakup tiga dimensi analisis yaitu mikrostruktur (analisis teks), mesostruktur (praktik wacana), dan makrostruktur (praktik sosial). Hasil penelitian dalam wacana “Turbulensi Kurikulum Merdeka” dari aspek kebahasaan ditemukan istilah-istilah yang dapat memperkuat pemahaman tentang kurikulum merdeka, dari aspek praktik wacana penggunaan gaya bahasa dapat memberikan pemahaman kepada pembaca tentang dinamika kurikulum merdeka, kemudian dari aspek praktik sosial pada wacana tersebut terdapat keterkaitan antar peran di dunia Pendidikan untuk saling bersinergi dalam menghadapi dan mengimplementasikan kurikulum merdeka